IMPLEMENTASI PEDOMAN KENDALI MUTU AUDIT-APARAT PENGAWASAN INTERN PEMERINTAH PADA INSPEKTORAT PROVINSI SULAWESI UTARA - Mewengkang, Sendy J.; Lambey, Linda; Saerang, David P. E. (Universitas Sam Ratulangi, 2016)
The purpose of this research is to know the Implementation of Audit Quality Control – Internal Auditing of Government Apparatus (PKMA-APIP) at Inspectorate of North Sulawesi Province. Procedures in PKMA-APIP consist of Strategic Plan Design, Audit Plan, Audit Action Plan Program Design, Audit Supervision, Audit Process, Audit Report, Feedback on Audit Report and Human Resources they are intended to ensure APIP professionalism implementation in enhancing supervising role quality. This study is a qualitative descriptive research. The result show that the implementation for audit quality control in the Inspectorate of North Sulawesi Province is not optimal and not appropriate perfectly. It is because the audit plan has not been implemented appropriate with PKMA-APIP, human resources are unqualified to fulfill existing workload, monitoring follow up results of the audit conducted by the unit performing the function of reporting is not maximized, unclear job description towards the unit managing administration and human resources, procedures provided in supporting the implementation of the tasks have not yet been implemented adequately and effectively to monitor the implementation of programs and activities (peer review). The monitor is to ensure and guarantee that the audit conducted by the Inspectorate of North Sulawesi Province meet the standard audit. Keywords : Audit, Quality Control, Government Internal Auditors